Implementasi Arah Kebijakan Pendidikan Prasekolah dan Respons Orang Tua terhadap Partisipasi Anak di Taman Kanak-Kanak - Wiyana As’ari; Winengan; Hadi Kusuma Ningrat (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The purpose of this study is to analyze the implementation of preschool education policy directions and parents’ responses to children's participation in kindergarten. The study employed a qualitative approach with a case study design. It was conducted in one kindergarten, involving five informants consisting of one principal, two teachers, and two parents. Data were collected through semi-structured interviews, non-participant observation, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The validity of the data was ensured through source and technique triangulation. The results indicate that informants generally have a good understanding of the importance of preschool education, and parents’ responses to children's participation in kindergarten tend to be positive. However, the implementation of preschool education policy directions has not been fully optimal because the policy remains advisory rather than mandatory, policy communication has not reached all parents effectively, and some parents still have limited understanding of the importance of preschool education. In addition, children's participation is influenced by socioeconomic factors and limited access to educational institutions. Therefore, improving the effectiveness of policy communication and strengthening support from various stakeholders are necessary to enhance children's participation in preschool education. This study is expected to serve as a reference for strengthening the implementation of preschool education policies in Indonesia.